Never enough : when achievement culture becomes toxic--and what we can do about it - Wallace, Jennifer Breheny (Portfolio/Penguin, 2023)
"In Never Enough, reporter Jennifer Breheny Wallace investigates the deep roots of toxic achievement culture. Drawing on interviews with families, educators, and psychologists, she offers a humane view of the crisis plaguing today's teens and a practical framework for how to help"--